Ionic Charge Storage in Diketopyrrolopyrrole-Based Redox-Active Conjugated Polymers - Samuel, Jibin J; Karrothu, Varun Kumar; Canjeevaram Balasubramanyam, Ram Kumar; Mohapatra, Aiswarya Abhisek; Gangadharappa, Chandrasekhar; Kankanallu, Varun Ravi; Patil, Satish; Aetukuri, Naga Phani B (Journal of physical chemistry. C, 2021)
Redox-active conjugated polymers are an emerging class of organic charge storage materials for lithium-ion batteries. The electron conducting conjugated backbone linking the localized redox moieties enables fast electron transfer kinetics. Polymers with redox moieties that have fast redox kinetics and high redox potentials with respect to Li+/Li while being stable under electrochemical environments are ideal for energy storage applications. In this work, we propose diketopyrrolopyrrole (DPP) as a suitable redox moiety for realizing redox-active conjugated polymer-based Li-ion cathodes. Li-ion batteries using DPP-based polymers proposed in this work show stable cycling up to 1000 cycles, a high rate performance with ∼70% capacity retention at a C-rate of 500 C, and reasonably high potentials of ∼2.2 V vs Li+/Li. We also demonstrate that these polymers could potentially find applications as cathode materials in other ion insertion batteries such as, for example, Na-ion batteries. The results of our work set an encouraging precedent for designing versatile, high energy density, and long-life charge storage materials based on DPP-based redox-active conjugated polymers.